CP-112 A multidisciplinary approach to antiretroviral simplification in HIV infected patients. (25th February 2017) - Valcarce, N; Alvarez, H; Garcia, JF; Rodríguez, I; Mariño, A
Abstract : Background: Simplification of antiretroviral treatment (ART) is an option to reduce pill burden, decrease drug toxicities, minimise drug interactions, improve adherence, preserve future treatment options and decrease healthcare costs, in the management of treatment experienced HIV infected patients with virological suppression Purpose: To investigate the effects of a multidisciplinary approach to simplify ART in treatment experienced HIV infected patients with virological suppression. Material and methods: This was a prospective, descriptive, observational study. ART simplifications from January 2015 to January 2016 by a multidisciplinary HIV unit (two infectious diseases doctors and a hospital pharmacist) in a second level hospital were included. The HIV unit identified patients who were the best candidates for undergoing ART simplification. Demographic and clinical characteristics, viral load, CD4 T cell count, toxicities, prior ART history, drug resistance testing, adherence and costs were recorded before and at least 24 weeks after simplification. Ease of administration, virological suppression maintenance, tolerability and toxicity, as well as cost savings arising from simplification, were analysed. Adherence was measured according to pharmacy dispensing records. Statistical analysis was performed using SPSS v21. Results: 56 ART simplifications in 56 HIV+ patients (15% of patients on ART). Median age was 50 years (IQR 45–53), 66% were men and 41% were CDC stage C. The average time since diagnosis was 10 years. 48% reduced drug exposure to a simpler maintenance regimen, 36% changed to a dual ART, 14% changed to a single tablet regimen and 1 patient changed to PI/r monotherapy. The median pill burden was 3 tablets (IQR 3–5) before and 2 tablets (IQR 1–3) after simplification. After switching, time of follow-up was 10.78±3.5 months. All patients showed suppressed viral loads (96% <20 copies/mL, 2 patients had 20–50 copies/mL) at the end of the study, and therefore maintained efficacy was demonstrated. Tolerance was considered successful after simplification and no adverse effects were reported throughout the study. 95% of patients were considered adherent. Overall simplification led to a cost reduction of €10 332/month, €123 984/year(p<0.05). Conclusion: A multidisciplinary approach contributed to ART simplification that not only maintained virological suppression and adherence but also prevented toxicities, facilitated administration and saved costs in treatment experienced HIV infected patients. No conflict of interest.